"Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Pendidikan Kewarganegaraan " - Hidayah, Fathul (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the effect of the Discovery Learning learning model using video media on the learning outcomes of fifth grade elementary school students. This type of research is quantitative research in the form of Pre-Experimental Design with the type of One Group Pretest-Posttest. The population of this study was the fifth grade students of SD N Adipuro. The sample used in this study was the fifth grade students of SD N Adipuro which consisted of 40 students using the collected sampling technique. In collecting data using observation techniques, and interviews Based on the results of the study, it is known that the learning outcomes of grade 5 students have increased through the application of discovery learning strategies. Through the discovery learning model, the students are more enthusiastic in participating in learning. So, based on the results of the research analysis conducted, it can be concluded that there is an influence of the Discovery Learning model using video media on the learning outcomes of fifth grade students at SDN Adipuro..